2005
DOI: 10.1161/01.cir.0000151805.86933.35
|View full text |Cite
|
Sign up to set email alerts
|

Drug Therapy in the Heart Transplant Recipient

Abstract: With improving survival, the heart transplant recipient faces an increasing number of medical problems caused by both aging and the cumulative complications of immunosuppressive drugs. 1 The availability of new drugs to treat infection, obesity, hypertension, hyperlipidemia, renal insufficiency, diabetes, osteoporosis, gout, and malignancies has resulted in the heart transplant recipient and their physicians facing an almost overwhelming number of important drug-drug interactions. In parts 1 through 3 of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 95 publications
0
66
0
4
Order By: Relevance
“…156,157 Although the majority of data in this population have been with simvastatin (5-20 mg daily) and pravastatin (20-40 mg daily), considerable controversy exists on which statin and what doses to use because of potential DDIs with the calcineurin inhibitors (eg, cyclosporine and tacrolimus) that could lead to myopathy or rhabdomyolysis. [153][154][155][156]158 CALCIneURIn InHIbItORS…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…156,157 Although the majority of data in this population have been with simvastatin (5-20 mg daily) and pravastatin (20-40 mg daily), considerable controversy exists on which statin and what doses to use because of potential DDIs with the calcineurin inhibitors (eg, cyclosporine and tacrolimus) that could lead to myopathy or rhabdomyolysis. [153][154][155][156]158 CALCIneURIn InHIbItORS…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“…Because of the metabolism of tacrolimus, the patterns of statin DDIs would be expected to be similar to those of cyclosporine. 158 Unfortunately, limited data exist on tacrolimus and statin interactions. One open-label evaluation of 13 healthy volunteers suggested that after 4 days of therapy with atorvastatin 40 mg daily, 2 doses of tacrolimus had no impact on the atorvastatin pharmacokinetics.…”
Section: Cyclosporine and Tacrolimusmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluvastatin, pravastatin, pitavastatin and rosuvastatin have less potential for interaction. 402 Tacrolimus is also metabolized by CYP3A4, but appears to have less potential for harmful interaction with statins than ciclosporin. Other drugs that influence CYP3A4 activity should be avoided if possible and used with extreme caution in patients receiving both calcineurin inhibitors and statins.…”
Section: Esc/eas Guidelinesmentioning
confidence: 99%
“…Это означает, что полученные результаты могут расцениваться как репрезентативные для всей российской популя-ции реципиентов сердца. Полученные в настоящем исследовании результаты близки к опубликованным данным, согласно которым распространенность АГ спустя 5 лет после трансплантации сердца состав-ляет от 50 до 95% [6,7].…”
Section: Discussionunclassified